Integrated Solar‐Driven Device with a Front Surface Semitransparent Catalysts for Unassisted CO2 Reduction (Adv. Energy Mater. 36/2022). Issue 36 (23rd September 2022) - Cheng, Wen‐Hui; Richter, Matthias H.; Müller, Ralph; Kelzenberg, Michael; Yalamanchili, Sisir; Jahelka, Phillip R.; Perry, Andrea N.; Wu, Pin Chieh; Saive, Rebecca; Dimroth, Frank; Brunschwig, Bruce S.; Hannappel, Thomas; et al.
Abstract : Unassisted CO2 Reduction In article number 2201062, Bruce S. Brunschwig, Thomas Hannappel, Harry A. Atwater, and co‐workers report a monolithic integrated photovoltaic‐driven electrochemical device for unassisted CO2 reduction with 5.9% direct solar‐to‐CO conversion efficiency and 50 h stability. The prism designs featuring structures to redirect sunlight into the bottom triple junction cell with reduced shadow loss represent a general approach to front illuminated photoelectrodes.